Factors influencing creative teaching among teachers in Islamic private schools in Kuala Lumpur - Hamed, Popoola Kareem; Preece, Abdul Shakour Duncan; Hashim, Che Noraini (2016)
Creativity is an essential element of teaching and learning that brings delight and meaningfulness to the classroom and to students‟ learning experiences. Recent calls in education for the implementation of authentic activities and real-world problem solving that promote student-engagement with curriculum content require more flexible and creative ways of teaching. Moreover, dissatisfaction with traditional methods of teaching among the students and teachers of Islamic schools is growing, as traditional pedagogy does not allow for critical and creative thinking. This leaves Muslim educators in a dilemma. This study aimed to investigate the factors influencing creative teaching among teachers of Malaysian Islamic private schools (IPS). The study employed a quantitative research methodology whereby a „questionnaire for creative teaching factors‟ was adapted and administered to 180 teachers from four selected IPS‟s, using a stratified random sampling technique. The data was then analysed using descriptive analysis, independent sample t-Test and ANOVA. The findings show that creative teaching is influenced by eight key factors: motivation, personal effort, learning attitude, teaching belief, school environment, teaching commitment, personal knowledge and growing-up experience. However, after ranking the factors, four main factors were identified that influence creative teaching, namely: personal efforts, teaching beliefs, teaching commitment and personal knowledge. In addition, the findings indicate that there were statistically significant differences between some of the factors influencing creative-teaching for teachers at IPS‟s, based on respondents‟ demographic details. Finally, the findings suggest that for creative teaching to bloom at IPS‟s there is a need for teams of experienced and creative professionals who can respond to a diverse range of learner needs and attitudes.